Chiari II Malformation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The theories of the basic embryological defect that lead to the Chiari II malformation are reviewed and a unified theory proposed from the Division of Pediatric Neurosurgery, The Laboratory for Oculo-Cerebrospinal Investigation, The Children's Memorial Medical Center and Northwestern University Medical School, Chicago, IL.